Influence of Magnus cylinder and variable angle flap on the aerodynamic performance of unmanned sailboat - Haoyun DENG; Dianzhu GUAN; Senmao LI; Xianhui WANG (Zhongguo Jianchuan Yanjiu, 2023)
ObjectiveThis paper aims to study and optimize the influence of Magnus airfoil and variable angle flaps on the aerodynamic performance of unmanned sailboats in order to improve the sailing efficiency. MethodsNACA 0021 is used as the basic airfoil for the mainsail, and the Magnus cylinder is coupled with the tip edge of the mainsail to analyze the influence of key parameters (i.e., diameter, position and gap) on the lift-drag characteristics of the airfoil. On this basis, a flap sail is embedded at the trailing edge of the mainsail to study the flow field conditions and lift-drag characteristics of the airfoil under different flap deflection angles, and its influence on the thrust performance of the unmanned sailboat.ResultsThe results show that under a large angle of attack, the Magnus cylinder has an improving effect on the aerodynamic performance of the airfoil; its lift-to-drag ratio is positively correlated with position and negatively correlated with diameter and gap within the studied range; diameter and gap have a greater effect on the aerodynamic performance of the airfoil than the position; the variable angle flap has a more obvious improving effect on the aerodynamic performance of the airfoil under a small angle of attack, and the lift-to-drag ratio is positively correlated with the flap deflection angle in a 0°–15° angle of attack; and within the studied range, the joint action of the Magnus cylinder and flap has a maximum improvement of 27% on the thrust coefficient of the sail, and the thrust coefficient is positively correlated with the flap deflection angle.ConclusionThe results of this study can provide references for the application of Magnus cylinders and embedded flap in the field of unmanned sailing.